Association between depressive symptoms and psychosocial factors and perception of maternal self-efficacy in teenage mothers - Lara, Ma Asunción; Patiño, Pamela; Navarrete, Laura; Hernández, Zaira; Nieto, Lourdes (2017)
Introduction. Teenage pregnancy is a national health priority. Having to deal with pregnancy during adolescence can cause the mother, at an already vulnerable age, to doubt her maternal capacity to cope with a challenge of this magnitude. The teenage mother’s assessment of her maternal self-efficacy is associated with her performance, in other words, the way she relates and responds to the needs of her infant, which has major implications for the latter’s development El embarazo adolescente es una prioridad nacional para la salud. Enfrentar un embarazo durante la adolescencia puede hacer que la madre, a una edad de por sí vulnerable, dude de su capacidad materna ante un reto de esta magnitud. La valoración que hace de su eficacia materna se asocia con su desempeño, esto es, con la manera de relacionarse y responder a las necesidades de su infante, misma que tiene consecuencias determinantes en el desarrollo de éste